Model-based development and test of device drivers - Stefan Ferstl (Fachhochschule Ingolstadt - University of Applied Sciences, 2007)
The development of device drivers in the automotive industry is often confronted with the problem of not yet available hardware, which can be used for testing. This paper describes how to build up a test environment in Simulink, which contains a model of the physical and logical behavior of an intelligent smart power switch that is used to control multiple bulbs in a car. To get a closed-loop simulation, a bulb model was developed, which calculates the current depending on voltage and temperature for diagnostic purposes. By using this configurable environment, it was possible to develop and test a driver with TargetLink, although the device, which it has to control, was not yet available. In order to get experience in HIL tests using the interface between CANoe and Simulink, this approach was analyzed in detail.
urn:nbn:de:bvb:573-283
Keywords: 650